Assessing the potential of coniferous greenery from logging residues in Latvia using a system dynamics model (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Latvia is the fourth most forested country in Europe. 52 % of the country’s area is covered by forest lands. Approximately 41 % of the forests are composed of conifers that are the most harvested among the tree species in Latvia. Therefore, as a result of logging, large amount of coniferous residues are created and abandoned in forests.  There are several alternatives for sustainable use of coniferous residues. Still, the exact quantity of the resource is not known. Thus, it is not clear, whether its amount is sufficient for products’ manufacturing. The aim of the study is to assess the potential of the coniferous greenery from logging residues’ extraction in Latvia. A system dynamic’s model that allows simulation of complex forestry processes depending on various endogenous and exogenous factors has been built for this purpose.